PERSIAPAN MAHASISWA MENGIKUTI PERKULIAHAN DI PROGRAM STUDI BIMBINGAN DAN KONSELING STKIP PGRI SUMATERA BARAT (Studi Deskriptif Analitis pada Mahasiswa Bimbingan dan Konseling STKIP PGRI Sumatera Barat) - Oktarina, Rini; Kasih, Fitria (Bimbingan dan Konseling, 2013)
This research aimed to describe: Preparing of the Students Following Lectures in Guidance and Counseling Program of STKIP PGRI West Sumatra, include: 1). Preparation of students before attending lectures, 2). Preparation of students as upper division lectures and 3).Preparation of students after attending the lecture. This research is a descriptive study.This study takes some of the student guidance and counseling STKIP PGRI West Sumatra which is used as research subjects. The technique used in the data collection in this study of non-test instruments, namely questionnaires. Sample collection with random sampling. Data analysis using the percentage formula. Results of research conducted can be described as follows: 1). Preparation of students before attending lectures in Guidance and Counseling Program of STKIP PGRI West Sumatra are included in good categories with a percentage of 60.00%, 2). Preparation of students when attended lectures in Guidance and Counseling Program of STKIP PGRI West Sumatra are included in good categories with a percentage of 54.17% and 3). Preparation of students after attending lectures in Guidance and Counseling Program of STKIP PGRI West Sumatra are included in good categories with a percentage of 46.67%. Conclusion: Preparation of the Students Following Lectures in Guidance and Counseling Program of STKIP PGRI West Sumatra are included in good categories. Researchers recommend to: Prodi BK business, in order to always provide motivation for students to keep and maintain a good preparation before, while and after following the lecture.